Reconstructing Post-Divorce Maintenance Based on Social Jurisprudence of Kiai Sahal Mahfudh: Transitional Alimony Offer - Viki Mayanfauki; Nur Lailatul Musyafa'ah; Anillahi Ilham Akbar (Al-Zahra : Journal for Islamic and Arabic Studies, 2026)
It is noted that structural poverty occurs as a result of divorce, which is predominantly occurring in women as the head of the family. The wife's financial dependence, the absence of standards, regulations and the post-talaq maintenance mechanism are the reasons for this to happen. Weak supervision also contributes to the neglect of obligations by the husband. This research aims to reconstruct the concept of post-talaq livelihood which is expected to be able to ensure that women's economy is rejected during the post-talaq adaptation period to break structural poverty. This study differs from previous studies by integrating classical Islamic jurisprudence with Kiai Sahal Mahfudh’s social fiqh framework and proposing the concept of transitional maintenance as a new model for developing post-divorce maintenance aimed at ensuring women's economic protection. The method used was library research with a normative approach based on classical fiqh literature, legislation, court decisions, and the works of Kiai Sahal Mahfudh. The data obtained were analyzed using a social fiqh framework that emphasizes the public interest, social justice, and the responsiveness of the law to social realities. The results of this study indicate that the concept of post-divorce maintenance, whether in the form of ‘iddah or mut’ah, is still often neglected due to a lack of oversight, its symbolic nature, and its inadequacy in ensuring women’s economic sustainability after divorce in a modern context. The findings indicate that Kiai Sahal Mahfudh's social fiqh, although it does not explicitly formulate the concept of "transitional maintenance" (al-nafaqah al-intiqāliyyah) as a legal term, provides the methodological foundation for reconstructing post-divorce maintenance in a way that promotes public welfare (maṣlaḥah) and social justice. Building upon this foundation, this study proposes the concept of "transitional maintenance" as a novel scholarly interpretation. It is a mechanism of temporary economic protection for divorced women during the adjustment period until they attain economic self-sufficiency.